Application of the doman method through encyclopedic intelligence bits for the Improvement of reading compression in the english language. - Infante Lima, Estefani Maribel; Vásquez Illescas, Joselyn Janeth (Machala : Universidad Técnica de Machala, 2021)
The main objective of this research is to improve reading comprehension through the application of the Doman Method by means of encyclopedic intelligence bits. Thanks to the review of previous studies, it is determined that for applying the Doman Method, the age, the active participation of the student, the time, the content, the attractions, and good quality materials are of utmost importance. The research is of qualitative paradigm, under a participatory action research design. The instruments applied for collecting the information were the observation guide, diagnostic test, and teacher interview. The results gotten guided the application of the Doman Method through the encyclopedic Intelligence Bits. The pedagogical proposal is based on four pedagogical suggestion classes directed to students of Fifth Year of General Basic Education. In conclusion, it is fundamental that the educational sector actors (parents, teacher, and student) work together in the new study modality to avoid the weaknesses in the English language teaching-learning macro skills.
El presente trabajo investigativo tiene como objetivo principal mejorar la compresión lectora en el idioma inglés, a través de la aplicación del Método Doman mediante Bits de inteligencia enciclopédicos en estudiantes de Quinto año de Educación General Básica. Gracias a la revisión de los anteriores estudios realizados, se determina que para la aplicación del Método Doman, es de suma importancia la edad, la participación activa del estudiante, el tiempo, el contenido, los materiales llamativos y de buena calidad. La investigación es de paradigma cualitativo, bajo un diseño de investigación- acción participativa, descriptiva. Los instrumentos aplicados para la recolección de la información fueron la guía de observación, test de diagnóstico y la entrevista al docente. Los resultados obtenidos guiaron a la aplicación del Método Doman mediante los Bits de Inteligencia enciclopédicos. La propuesta pedagógica se basa en cuatro clases de asesoramiento pedagógico dirigidos a estudiantes de Quinto Año de Educación General Básica, en conclusion es vital que los actores del sector educativo (Padres de familia, docente y estudiante) trabajen en conjunto en la nueva modalidad de estudio, para evitar que el proceso de la enseñanza-aprendizaje del idioma inglés se desarrolle con debilidades en las macro destrezas.
Keywords: METHOD; ENCYCLOPEDIC; TIME; INTELIGENCE